Surgical ablation for atrial fibrillation during isolated coronary artery bypass surgery. (30th October 2019) - Suwalski, Piotr; Kowalewski, Mariusz; Jasiński, Marek; Staromłyński, Jakub; Zembala, Marian; Widenka, Kazimierz; Brykczyński, Mirosław; Skiba, Jacek; Zembala, Michał Oskar; Bartuś, Krzysztof; Hirnle, Tomasz; Dziembowska, Inga; et al.
Abstract: : OBJECTIVES: Our goal was to evaluate early sequelae and long-term survival in patients undergoing isolated coronary artery bypass grafting (CABG) with concomitant surgical ablation for atrial fibrillation (AF). METHODS: Procedural data from KROK (Polish National Registry of Cardiac Surgery Procedures) were collected. A total of 7879 patients with underlying AF underwent isolated CABG between 2006 and 2018 in 37 reference centres across Poland. The mean follow-up was 4.7 ± 3.5 years [median (interquartile range) 4.3 (1.7–7.4)]. Propensity score matching and Cox proportional hazards models were used to compare isolated CABG + ablation with isolated CABG. RESULTS: Of the included patients, 346 (4.39%) underwent surgical ablation. Patients in this group were significantly younger (66.4 ± 7.5 vs 69.2 ± 8.2; P < 0.001) but had a non-significant, different baseline surgical risk (EuroSCORE: 2.11 vs 2.50; P = 0.088). After a rigorous 1:3 propensity matching (LOGIT model: 306 cases of isolated CABG + ablation vs 918 of isolated CABG alone), surgical ablation was associated with a lower 30-day risk of death [risk ratio 0.37, 95% confidence interval (CI) 0.15–0.91; P = 0.032] and multiorgan failure (risk ratio 0.29, 95% CI 0.10–0.94; P = 0.029). In the long term, surgical ablation was associated with a significant 33% improved overall survival rate: hazard ratio 0.67, 95% CI 0.49–0.90; P = 0.008. The benefit of ablation was sustained in the subgroups but was most pronounced in lower risk older patients (age >70 years, P = 0.020; elective status, P = 0.011) with 3-vessel disease ( P = 0.036), history of a cerebrovascular accident ( P = 0.018) and preserved left ventricular function [left ventricular ejection fraction >50%; P = 0.017; no signs of heart failure (per New York Heart Association functional class); P = 0.001] and those undergoing on-pump CABG ( P < 0.001). CONCLUSION: Surgical ablation for AF in patients undergoing isolated CABG is safe and associated with significantly improved long-term survival.